The position of Ibn al-Jawzi T 597 AH / 1201 AD from Greek philosophy - his approach to criticism - his religious doctrine - and the philosophy of history - - Al - Husseini, Mohammed Ayed (Journal of Humanities & Social Sciences, 2017)
This study presented an objective view on the employment of historical work with the intellectual side of Islamic thought scholars in the Islamic era. It is specialized here in the 6th / 12th century AD, which witnessed a great change in the field of thought and assimilation of the news and science.Therefore, in this study, it is necessary to deduce the intellectual vision of Ibn al-Jawzi, whether through his position on Greek philosophy or his ideological ideas of virtue and ethics, let alone his permanent abandonment of religion as a law to which he is subject.Therefore, the research provides more than a vision about the ideas of Ibn al-Jawzi on the topics of historical, philosophical and monetary thought, and his position on the books of the former and contemporaries. Even if the ecclesiastical religion covered most of his works, we find him sometimes inclined towards philosophical visions.And is different in other positions and this is not new to the historians of the sixth century AH, and perhaps the multiplicity of religious groups and doctrinal trends have had an impact on the impact of the writings of historians of this period in which Ibn al-Jawzi rejected the great intransigence of most of what he saw a change in the analysis and take out the legitimate rule of things Religious.
Keywords: Ibn al-Jawzi; criticism; Greek philosophy; history